Efficiency Map and Weighted Average Efficiency for synchronous machines for Hydropower Plants. - BORTONI, Edson da Costa (2019)
In recent years there has been a claim of evaluating the weighted average efficiency of synchronous machines for hydro-generation application instead of a single value at the rated condition in order to consider the most frequent loadings. This work contributes to mapping the efficiency of a synchronous machine limited by its capability chart. In a second opportunity, a histogram of an operating generator is obtained. The crossing of the aforementioned information allows for the obtaining of a weighted average efficiency in full capable operation. Some aspects that lead the machine to operate out from the rated point are raised along with the efficiency-oriented design issues. The theory involving losses and capability chart of the machine is presented. The behavior of the losses in loadings different than the rated one is presented as well in which a theoretical model is included to achieve the efficiency of any loading by using the rated load efficiency obtained by an approach of an infrared-based calorimetric test. The proposed methodology is applied to the existent machine.